2013
DOI: 10.1111/jlme.12054
|View full text |Cite
|
Sign up to set email alerts
|

Biobanking, Consent, and Certificates of Confidentiality: Does the ANPRM Muddy the Water?

Abstract: Précis In its Advanced Notice of Proposed Rule Making (ANPRM), the US Department of Health and Human Services proposed substantial changes to how biospecimen research is treated under the regulations governing human subjects research. Currently, much of this research can be conducted without consent because it may not be considered “human subjects” research, is considered exempt, or consent may be waived. Responding to criticisms that scientific changes have made biospecimen research riskier than contemplated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Notably, the rule change would neither apply to the BioTrust's legacy collection of DBS nor to existing collections in biobanks nationwide. The summer 2013 issue of the Journal of Law, Medicine and Ethics highlights challenges associated with implementing the proposed changes to the Common Rule, including implications for certificates of confidentiality (Williams and Wolf 2013) and IRB reforms (Lidz and Garverich 2013). Our study informs this unfolding discussion, since popular attitudes toward the BioTrust may well presage those that will arise in future cases of research involving broad consent and de-identified biospecimens.…”
Section: Discussionmentioning
confidence: 85%
“…Notably, the rule change would neither apply to the BioTrust's legacy collection of DBS nor to existing collections in biobanks nationwide. The summer 2013 issue of the Journal of Law, Medicine and Ethics highlights challenges associated with implementing the proposed changes to the Common Rule, including implications for certificates of confidentiality (Williams and Wolf 2013) and IRB reforms (Lidz and Garverich 2013). Our study informs this unfolding discussion, since popular attitudes toward the BioTrust may well presage those that will arise in future cases of research involving broad consent and de-identified biospecimens.…”
Section: Discussionmentioning
confidence: 85%
“…Such deterrence, in turn, would sabotage genetic research efforts dependent on the availability of large number of genetic samples. 146 Notions of justice may also be implicated, as genetic research participants would be at greater risk of having their genetic data summoned than other litigants. This would do a disservice to people who volunteered to participate in research for the public good, and violate the idea that all litigants—regardless of their genetic testing history—are equal under the law.…”
Section: The Future Of Behavioral Genetic Evidence In Courtmentioning
confidence: 99%
“…However, neither the regulations for Institutional Review Boards nor guidance for NIH-funded studies require that biobanks and investigators secure Certificates of Confidentiality. 146 As a result, the certificate mechanism has been significantly under-utilized by biobanks (a 2003 study found that only 1 of 12 major biobanks in the U.S. had obtained a certificate, and only about quarter of IRBs would require or recommend it). 146,149 We have yet to see whether the NIH will endorse—and implement—the recommendation of the planners of the All of Us Research Program that all users of identifiable data be required to secure a certificate.…”
Section: The Future Of Behavioral Genetic Evidence In Courtmentioning
confidence: 99%
See 1 more Smart Citation
“…Some articles pointed out that this distinction could have unintended consequences and argued that treating biospecimens as unique required strong ethical reasoning that the NPRM did not provide (Williams and Wolf 2013; Robertson and Loe 2016). Although the NPRM cited surveys that indicated that the public wanted consent for biospecimen research, some argued that public opinion should not be the only guiding principle for policy (Robertson and Loe 2016).…”
Section: A Proposal For Future Revisions To the Common Rulementioning
confidence: 99%